2016
DOI: 10.1007/s00330-016-4518-9
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided percutaneous biopsy of solitary pulmonary lesions using a 1.0-T open high-field MRI scanner with respiratory gating

Abstract: • MRI-guided percutaneous lung biopsy using a 1.0-T open MR scanner is feasibility. • 96.9 % differentiation accuracy of malignant and benign lung lesions is possible. • No serious complications occurred in MRI-guided lung biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The first MRI-guided clinical trials were reported in 1986 (13). Since then, MRI-guided clinical applications have been successfully applied to lesions in various anatomical regions, such as pancreatic, breast, prostate, lung tumor, and renal tumor lesions (14)(15)(16)(17)(18). After ∼20 years of clinical use, MRIguided breast biopsy has evolved into a routine method in Western European countries (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The first MRI-guided clinical trials were reported in 1986 (13). Since then, MRI-guided clinical applications have been successfully applied to lesions in various anatomical regions, such as pancreatic, breast, prostate, lung tumor, and renal tumor lesions (14)(15)(16)(17)(18). After ∼20 years of clinical use, MRIguided breast biopsy has evolved into a routine method in Western European countries (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The needle entry point was determined by MRI with a matrix grid made of fish oil capsules, details of which have been reported elsewhere . The approach angle and distance (from the skin to the lesion) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) offers many inherent advantages over CT and US in terms of superior soft‐tissue contrast resolution, blood flow‐empty action, a nonionizing nature, and direct multiplanar capabilities. MR guidance has been successfully implemented for percutaneous biopsy and various therapies . Thus, the purpose of this study was to prospectively evaluate the safety and accuracy of MRI‐guided percutaneous coaxial cutting needle biopsy of pancreatic lesions using an open 1.0T high‐field MR scanner.…”
mentioning
confidence: 99%
“…Enhanced chest CT is recommended at 1, 3,6,9,12,18,24,30,36,42,48,54, and 60 months after implantation. After five years, a chest CT scan should be taken once a year.…”
Section: Follow-upmentioning
confidence: 99%